The Detrimental and Beneficial Functions of Macrophages After Cochlear Injury - Zhang, Yuan; Li, Yiyuan; Fu, Xiaolong; Wang, Pengjun; Wang, Qin; Meng, Wei; Wang, Tian; Yang, Jianming; Chai, Renjie (Frontiers in Cell and Developmental Biology, 2021)
Macrophages are the main intrinsic immune cells in the cochlea, they can be activated and play a complicated role after cochlear injury. Many studies have shown that the number of macrophages and their morphological characteristics within the major cochlear partitions undergo significant changes under various pathological conditions including acoustic trauma, ototoxic drug treatment, age-related cochlear degeneration, selective hair cell and spiral ganglion damage, and surgical wounds. However, the exact role of these macrophages after cochlear injury is still unclear. Regulating the migration and activity of macrophages may be a therapeutic approach to reduce the risk or magnitude of trauma-induced hearing loss, and this review highlights the role of macrophages on the peripheral auditory structures of the cochlea and elucidate the mechanism of macrophage injury and the strategies to reduce the injury by regulating macrophage.